N-Phenyl-2-(1,2,3,4-tetrahydronaphthalen-1-ylidene)hydrazinecarbothioamide - Adriano Bof de Oliveira; Bárbara Regina Santos Feitosa; Christian Näther; Inke Jess (Acta Crystallographica Section E, 2014)
The conformation of the title molecule, C17H17N3S, is stabilized by an intramolecular N—H...N hydrogen bond involving the azometinic group. The dihedral angle between the two aromatic rings is 36.49 (06)°. The non-aromatic ring of the tetralone substituent adopts a sofa conformation. In the crystal, molecules are linked by pairs of N—H...S hydrogen bonds related via centres of symmetry, forming dimers.